EVALUATION OF MORPHOLOGICAL AND IMMUNOHISTOCHEMICAL CHANGES OF BREAST CARCINOMAS AFTER NEOADJUVANT SYSTEMIC THERAPY - V. О. Bashlyk; V. F. Semiglazov; A. G. Kudaybergenova; A. S. Artem'eva; T. Yu. Semiglazova; V. S. Chirskiy; A. V. Komyakho; P. V. Krivorot'ko; V. V. Klimenko; Sh. M. Khadzhimatova; A. I. Tseluyko; S. S. Ereschenko (ABV-press, 2018)
Complete clinical response (determined by palpation, instrumental methods, and macroscopic examination) does not always imply the achievement of pathologic complete response. Correlation coefficient between complete clinical and complete pathologic responses is 0.6-0.7. Objective: to choose an optimal method for the assessment of residual tumor that will provide objective information on the efficacy of various neoadjuvant systemic therapy (NST) regimens. Materials and methods. We investigated trepanobiopsy samples of breast tumors collected prior to NST initiation and tissue samples collected during surgery after NST completion. The following parameters were evaluated: tumor histological type, hormonal receptor status, Ki-67 and HER2 expression, tumor cell density and the dynamics of these parameters in response to NST. Therapeutic pathomorphosis was estimated using ypTNM, Miller-Payne and RCB grading systems. Results. We observed various changes in the immunophenotypic profiles of the tumors in response to NST: luminal B subtype (HER2-) can become luminal A subtype due to decreased Ki-67 level and triple negative due to the loss of hormone receptors expression; triple negative breast cancer can acquire expression of hormone receptors and become luminal B subtype (HER2-).Conclusion. Integral assessment of therapeutic pathomorphosis using various grading systems (Miller-Payne, ypTNM and RCB) provides objective information on the residual tumor status. Pathomorphological assessment of residual tumor is an important component in the initial evaluation of various NST regimens efficacy.